Cardiac Angiosarcoma. A Review - Murinello, A (2012)
Based on a case of a patient with angiosarcoma (AS) of the right atrium with superior vena cava syndrome associated with urticaria and polyarthralgias, who died soon after surgery, the authors present a brief review of the subject of cardiac AS, an extremely rare pathology, usually diagnosed late due to its non-specific symptomatology. Several topics are discussed, including mechanisms of clinical manifestations caused by blood flow obstruction and valve dysfunction, local invasion with arrhythmias and pericardial effusion, embolic phenomena and constitutional symptoms. Imaging and histopathologic methods of diagnosis are considered, as well as references to cytogenetic analysis. Surgery is the first treatment choice, but heart AS are frequently not completely resectable and concomitant metastases at the time of surgery are common, both usually leading to a dismal prognosis. Chemotherapy, radiotherapy and even heart transplantation do not substantially improve the survival of these patients. Urticaria is not generally assumed by most authors to be associated with malignancy, but there are rare reports of its association with some malignant tumors.